Rhodium(III)‐Catalyzed Activation of C sp 3H Bonds and Subsequent Intermolecular Amidation at Room Temperature1. Issue 32 (15th July 2015) - Huang, Xiaolei; Wang, Yan; Lan, Jingbo; You, Jingsong
Abstract Disclosed herein is a RhIII‐catalyzed chelation‐assisted activation of unreactive C<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj270cczsc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> sp 3</alternatives>H bonds, thus enabling an intermolecular amidation to provide a practical and step‐economic route to 2‐(pyridin‐2‐yl)ethanamine derivatives. Substrates with other N‐donor groups are also compatible with the amidation. This protocol proceeds at room temperature, has a relatively broad functional‐group tolerance and high selectivity, and demonstrates the potential of rhodium(III) in the promotive functionalization of unreactive C<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj270ccztx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> sp 3</alternatives>H bonds. A rhodacycle having a SbF6− counterion was identified as a plausible intermediate.